2017
DOI: 10.9778/cmajo.20160076
|View full text |Cite
|
Sign up to set email alerts
|

Added sugar in the packaged foods and beverages available at a major Canadian retailer in 2015: a descriptive analysis

Abstract: Background: Excess consumption of added sugars has been associated with a variety of health problems, but there is little information available characterizing added sugar in the Canadian food supply. This study examined the presence and types of added sugars in the packaged food and beverage products available at a major Canadian grocery retailer. Methods:We searched the ingredients lists of over 40 000 packaged food products available for sale in March 2015 for a variety of added sugar terms. Proportions of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 31 publications
4
20
0
Order By: Relevance
“…Furthermore, given the current nature of the North American food supply, the major sources of added dietary sugars are derived from relatively isotopically enriched C 4 plants (e.g. corn, sugar cane) (Acton, Vanderlee, Hobin, & Hammond, ; USDA Economic Research Service, ), therefore the 13 C enrichment of PAM and other lipogenesis products may be useful biomarkers of added dietary sugar intake.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, given the current nature of the North American food supply, the major sources of added dietary sugars are derived from relatively isotopically enriched C 4 plants (e.g. corn, sugar cane) (Acton, Vanderlee, Hobin, & Hammond, ; USDA Economic Research Service, ), therefore the 13 C enrichment of PAM and other lipogenesis products may be useful biomarkers of added dietary sugar intake.…”
Section: Discussionmentioning
confidence: 99%
“…These were mainly found in the “beverages” group, “milk and dairy products”, “sugar and sweets” and “other food groups”. In Canada, Acton et al [ 31 ] analyzed 40,000 processed food products available for sale in 2015 and found that 66% contained at least one type of added sugar. In the USA, it was estimated that 68% of available processed foods and beverages contain caloric sweeteners (i.e., added sugars), 74% comprise both caloric and LNCS and 5% include only LNCS [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The average free sugar of CSSBs in the UK was 30.1±10.7 g/330 mL. 8 In Canada, the mean total sugar of pop/soda and iced teas with added sugar was 10.6±5.0 g/ 100 mL, 23 while in the USA the median added sugar content in caloric sodas/energy drinks was 11.3 g/ 100 mL. 12 The high sugar content suggested that there is a global challenge, including China, to control the high levels of sugar in CSSBs.…”
Section: Discussionmentioning
confidence: 99%